Construction of an evaluation scale of emotional intelligence for children in the elementary education - Moore Infante, Catalina; Soto, J. Mauricio (Revista de Psicología, 1999)
The purpose of the present study is to construct a Scale to Evaluate Emotional Intelligence in school children between first to fourth grade in the city of Concepcion (Chile). This is motivated by the absence of other instruments statistically valid and reliable to measure this concept, and pretends to be a contribution to potenciate the child emotional development, in the context of the Tranversal Objectives of the Chilean Educational Reform.